The effects of exercise on beef cattle health, performance, and carcass quality; and the effects of extended aging, blade tenderization, and degree of doneness on beef aroma volatile formation - Gerlach, Bryce Mark (Kansas State University, 2014)
Two experiments were conducted to evaluate the effects of exercise on feedlot cattle well-being, growth performance, and carcass characteristics (Experiments 1 and 2). Additionally, two experiments assessed the volatile compound profiles of beef in response to various postmortem processes (Experiments 3 and 4). Experiment 1 compared heifers (n=30) assigned to either a sedentary treatment or an exercise regimen 3 times/wk (20 min/d for the first 2 wk, 30 min/d for the next 2 wk, and 40 min/d for the final wk). Exercised heifers showed decreased blood insulin, daily gains, final body weights, and lower numerical yield grades in conjunction with decreased a* and b* color values of longissimus muscle lean. Experiment 2 exposed steers (n=419) to 1 of 4 treatments; not exercised (CON), or exercised 3 times/wk by animal handlers for 20-30 min for the first 10 wk (EARLY), the last 7 wk (LATE), or for the entire 116 d finishing period (ALL). EARLY treatment cattle exhibited a decrease in blood insulin while EARLY and ALL treatment cattle produced carcasses with decreased marbling scores in comparison to CON cattle. Experiment 3 assessed the volatile compounds generated by raw and cooked beef gluteus medius steaks (n=30) subjected to blade tenderization and aging times ranging from 5 to 61 d. Raw steaks aged longer than 19 d produced greater concentrations of heptanal, octanal, and nonanal than raw steaks aged 5 d, but cooked steaks showed no change in these compounds in response to aging. Additionally, blade tenderization reduced the concentrations of lipid oxidation and Maillard reaction products in cooked steaks. Experiment 4 investigated cross-sections, external, and internal locations of beef longissimus lumborum steaks (n=54) cooked to 63, 71, or 77 °C and aged for 5, 21, or 37 d. External locations generated aldehydes in greater amounts than internal locations while pyrazines are produced exclusively at external locations. Increases in degree of doneness increased all aldehydes, except nonanal, in steak cross-sections. Aldehydes, except hexanal and octanal, generated from external locations became similar to internal locations as aging times increased. Pyrazines from external locations were reduced by increased aging times.
Keywords: Aging; Aroma; Beef; Blade tenderization; Degree of doneness; Exercise; Animal Sciences (0475)